A novel methodological approach for achieving £/MWh cost reduction of CO2 capture and storage (CCS) processes. (1st November 2017) - Cabral, Renato P.; Mac Dowell, Niall
Highlights: Thermodynamic analysis to improve oxy-CCS efficiency. 2nd law analysis quantifies potential for improvement. Exergy Destruction analysis identifies targets for improvement. Results in 3% increase in efficiency, 15% reduction in capital cost. This equates to a 15% reduction in the £/MWh cost of CCS electricity. Abstract: Carbon capture and storage is widely recognised as essential for the cost effective decarbonisation of the power and industrial sectors. However its capital and operating costs remain a barrier to deployment, with significant reduction in the cost per unit of decarbonised product considered vital. In the context of power generation, this is best expressed in terms of cost per MWh of electricity generated. To achieve a meaningful reduction in the cost of low carbon electricity, capital costs must also be reduced. Thus, this work presents a novel approach for identifying system improvements via a combination of process integration and intensification based on minimisation of thermodynamic losses. Application of this methodology to an oxy-combustion CCS process led to a 3% increase of net efficiency and a 13% reduction of £/MWh of electricity.